Syntheses, Characterization and biological Activity of a new ligand [4-[(1E)- ethylideneamino]-5-phenyl-4H-1,2,4-triazole-3-thiol with some transition metals complexes - Hassan, Farah (University of Thi-Qar Journal of Science, 2013)
Anew Ligand 4-[(1E)-ethylideneamino]-5-phenyl-4H-1,2,4-triazole-3-thiole with its(CrCl3.6H2O,FeCl3.6H2O,CoCl3,NiCl2.6H2OandCuCl2.6H2O)complexes were synthesized .The authenticity of the ligand and its transition metal complexes were established by elemental analyses, conductance, as well as spectroscopic (IR, 1HNMR, mass It may be concluded that the ligand coordinate through Nitrogen(N1) and sulfer(S12) atoms as shown in figure (1). This view is further supported by the appearance of a band corresponding to the metal–nitrogen stretching at 410–555 cm–1 in the complexes. the Ni and Cu atoms leading to the formation tetrahedral geometry .Octahedral geometry was proposed for the(Cr(III),Fe(III) and Co(III) prepared complex. Figure(2). All complexes and their parent organic moiety have been screened forantibacterial (Table4) by using spread method and measurement inhibition zone by using (DMSO). this studying showed positivity results. By appear lager inhibition zone against E-coli and staph aurens. Figure(3)